Modelling trade-offs between livelihoods and wetland ecosystem services: the case of Ga-Mampa wetland,South Africa - (:unkn) unknown (My University, 2010)
This paper presents an integrated dynamic simulation model that represents the functioning of a small South African wetland. The model was developed using the STELLA platform and comprises six interactive sectors namely: hydrology, crop production, crop economics, use of natural wetland resources, land use decision and community well-being. These sectors are inter- linked and changes in one sector impact on other sectors through feedback loops between sectors. Key parameters in the model are demand for food, demand for income, and biophysical drivers (soils, rainfall, groundwater and surface flows). Taking into account these factors, the local community makes choices about uses of different categories of land and water resources available to them (irrigation scheme and wetland). These activities impact on the wetland functioning, which in turn influences economic returns of wetland related activities and ultimately livelihoods. The model is used to simulate several land management options under various localised scenarios of global changes.
Keywords: African Research